2010
DOI: 10.1007/s10653-010-9335-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on arsenic and humic substances in alluvial aquifers of Bengal delta plain (NW Bangladesh), Chianan plain (SW Taiwan) and Lanyang plain (NE Taiwan): implication of arsenic mobilization mechanisms

Abstract: Humic substances in groundwater and aquifer sediments from the arsenicosis and Blackfoot disease (BFD) affected areas in Bangladesh (Bengal delta plain) and Taiwan (Lanyang plain and Chianan plain) were characterized using fluorescence spectrophotometry and Fourier transform infrared (FT-IR) spectroscopy. The results demonstrate that the mean concentration of As and relative intensity of fluorescent humic substances are higher in the Chianan plain groundwater than those in the Lanyang plain and Bengal delta pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Geochemical studies of the Chia-Nan Plain region suggested saturation of Fe-and Mn-bearing carbonate, sulfides, and oxides in the groundwater of the region (Nath et al 2008;Reza et al 2010). Because of the difference in solubility of iron versus arsenic sulfides, precipitation of iron sulfide may remove sulfide from solution but not arsenic if precipitation rates were fast.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Geochemical studies of the Chia-Nan Plain region suggested saturation of Fe-and Mn-bearing carbonate, sulfides, and oxides in the groundwater of the region (Nath et al 2008;Reza et al 2010). Because of the difference in solubility of iron versus arsenic sulfides, precipitation of iron sulfide may remove sulfide from solution but not arsenic if precipitation rates were fast.…”
Section: Discussionmentioning
confidence: 99%
“…It may also indicate that the state of presence of Mn or Fe 2 O 3 in the sediments might be in the form of adsorbed phases on clay mineral surfaces, or as distinct phases whose particle size is within the clay mineral range. Field data collected from Chia-Nan Plain area showed poor correlation among Fe, As, and pH, and it was attributed to various biogeochemical reactions, mineral precipitation and dissolution, and saltwater intrusions that affect the chemical evolution of groundwater locally (Nath et al 2008;Reza et al 2010). However, this research showed that aquifer and aquitard materials as well as their physical and chemical properties may also need to be considered in studying As transport and retention.…”
Section: Arsenic Adsorption Studymentioning
confidence: 99%
See 1 more Smart Citation
“…8. Bands at 3,400, 2,927, 1,600, 1,590 and 1,028 cm -1 were assigned to (O-H stretching), aliphatic C-H stretching, aromatic C=C stretching, ketone and ether, respectively (Niemayer et al 1992;Miano and Senesi 1992;Reza et al 2010c). However, some differences can also be noticed.…”
Section: Fluorescence and Infrared Spectra Of Humic Substancesmentioning
confidence: 99%
“…When the sulfide oxidation is the dominant process of the passing of As to its aqueous forms, a positive correlation can be found between the concentrations of (SO 4 2− ) and (As) (Smedley and Kinniburgh 2002). In the sedimentary basins where the groundwater has a neutral pH and reducing environment associated with the presence of fresh organic matter, the geochemical environment is a determining factor for the solubility of arsenic (Selim et al 2010). The basic trigger mechanism for the dissolution of As in porewaters environments of sedimentary basins, with neutral pH and reducing geochemical environments, can be associated to reduction-related dissolution of Fe and Mn oxides minerals, which results in the migration of As(III), Fe(II) and Mn(II) into the aqueous phase where they can reach high concentrations of these elements with a positive correlation between them (Smedley and Kinniburgh 2002), while the concentrations of (SO 4 2− ) remains low (less than 1 mg/L).…”
Section: Introductionmentioning
confidence: 99%